2020
DOI: 10.3389/fpls.2020.00440
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Removal of N-Terminal Fusion Domains From Recombinant Target Proteins Produced in Nicotiana benthamiana

Abstract: Plants show great potential for producing recombinant proteins in a cost-effective manner. Many strategies have therefore been employed to express high levels of recombinant proteins in plants. Although foreign domains are fused to target proteins for high expression or as an affinity tag for purification, the retention of foreign domains on a target protein may be undesirable, especially for biomedical purposes. Thus, their removal is often crucial at a certain time point after translation. Here, we developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…CBM3 tightly binds to microcrystalline cellulose (MCC) beads. The SUMO domain of Brachypodium is used to release the C-terminal region containing CES3 from the full-length recombinant protein by proteolysis, using bdSNEP1, a SUMO protease from Brachypodium 33 . The His-tag of 6 histidine residues (His) was used for western blot analysis and purification using the Ni 2+ -NTA affinity column.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CBM3 tightly binds to microcrystalline cellulose (MCC) beads. The SUMO domain of Brachypodium is used to release the C-terminal region containing CES3 from the full-length recombinant protein by proteolysis, using bdSNEP1, a SUMO protease from Brachypodium 33 . The His-tag of 6 histidine residues (His) was used for western blot analysis and purification using the Ni 2+ -NTA affinity column.…”
Section: Resultsmentioning
confidence: 99%
“…The upper band corresponds to the full-length recombinant protein. A previous study showed that a recombinant protein containing the SUMO domain is subject to proteolytic cleavage at the C-terminal end of the SUMO domain by an unknown endogenous protease 33 . Thus, BNCS:CES3:His might have been subject to proteolysis at the C-terminal end of the SUMO domain to give a truncated polypeptide at the 51 kD position 33 .…”
Section: Resultsmentioning
confidence: 99%
“…We also incorporated the M-domain of the human receptor-type tyrosine-protein phosphatase C, containing four N-glycosylation sites, as it reportedly enhances the expression of ER-localized proteins remarkably in plants (Kang et al, 2018 ). After the M domain, we added the bdSUMO ( Brachypodium distachyon Small Ubiquitin-like Modifier) and a GG (Gly-Gly) motif, providing the binding site for the protease bdSENP1 ( Brachypodium distachyon Sentrin/SUMO-specific protease-1) for cleavage immediately after the GG motif, thereby helping to achieve the removal of the unnecessary BiP signal peptide, M domain, and bdSUMO after the production of GtCel12A in the ER ( Figure 1A ) (Islam et al, 2019 , 2020 ). After incorporating the GtCel12A coding sequence, we added the coding sequence of CBM3 (family 3 cellulose-binding module) that irreversibly binds to MCC beads and has been previously used as an affinity tag (Islam et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The constructs BiP-M-bdSUMO-GtCel12A-CBM3-HDEL or BiP:bdSENP1:HA (Islam et al, 2020 ) were transformed into Agrobacterium tumefaciens (EHA105). A. tumefaciens cells harboring binary vector constructs were introduced into N. benthamiana leaves via syringe infiltration as described previously (Islam et al, 2019 ; Razzak et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation